A nonlinear edge –preserving smoothing filter for edge detection on color and gray satellite images - Hamdan, Suhad A. (Iraqi Journal of Physics, 2019)
A nonlinear filter for smoothing color and gray imagescorrupted by Gaussian noise is presented in this paper. The proposedfilter designed to reduce the noise in the R,G, and B bands of thecolor images and preserving the edges. This filter applied in order toprepare images for further processing such as edge detection andimage segmentation.The results of computer simulations show that the proposedfilter gave satisfactory results when compared with the results ofconventional filters such as Gaussian low pass filter and median filterby using Cross Correlation Coefficient (ccc) criteria.